Learners’ Collaboration Experiences and Perceptions of Teamwork Strategies in an Online Graduate Class - MELİS DİLEK; Olgun Sadik; Curtis Jay Bonk (Journal of the Scholarship of Teaching and Learning)
Working together in teams has been an increasingly implemented strategy in online learning environments to construct and negotiate new knowledge. In this study, seven different teamwork strategies were selected from the literature and implemented in an online graduate course at a private university in Turkey to understand learners' perceptions and reveal insights into their experiences. Data collected from learner interviews, document analyses, and observations showed that participants had varying insights and perceptions about different teamwork strategies. However, working with the same team members throughout the semester increased team trust and promoted a sense of belongingness to the teams. Participants expressed positive attitudes about the grouping strategy based on working hours and styles; however, experienced learners in their graduate studies stated their dissatisfaction regarding teamwork strategies. The participants could not systematically implement distributed leadership. Instead, personality and prior experiences in graduate studies built an invisible leadership in the teams. Peer assessment was found to be an ineffective strategy for the participants who have inner motivation and responsibility.